Education, Competence Development and Career Trajectories Analysing Data of the National Educational Panel Study (NEPS) - Weinert, Sabine; Blossfeld, Gwendolin Josephine; Blossfeld, Hans-Peter (Methodology of Educational Measurement and Assessment, 2023)
This Open Access book presents the results of an interdisciplinary research program to utilize data from the multicohort German National Educational Panel Study (NEPS), which included over 100.000 participants in six nationally representative panel studies. Renowned researchers from the fields of sociology, psychology, educational science, economics, and survey methodology have used the (longitudinal) data for their substantive and/or methodological questions and present important results of their research projects. This edited volume contains contributions from the following four topics: (1) Competence Development: Individual Characteristics, Learning Environments, and other Contextual Factors, (2) Educational Transitions and Pathways: Influencing Factors and Outcomes, (3) Vocational Training and Labour Market, and (4) Individuals with Migration Background. It provides essential insights for researchers, postdocs, PhD students, and university students of different scientific disciplines interested in educational sciences as well as for policy makers who have to deal with educational problems in modern societies.